Assessing suitability of commercial fibre reinforced plastic solar still for sustainable potable water production in rural India through detailed energy-exergy-economic analyses and environmental impacts. (1st October 2021) - Sharon, H.; Prabha, C.; Vijay, R.; Niyas, A. Mohammed; Gorjian, Shiva
Abstract: Fibre reinforced plastic (FRP) basin solar still is manufactured and marketed commercially in developing/underdeveloped nations. Unfortunately, these commercial units have not been widely adopted by the public due to its low water productivity. In the present investigation, an effort has been made to assess the performance and enviro-economic aspects of the commercial unit and its low-cost improved versions under Coimbatore climatic conditions through real-time experiments and mathematical models, respectively. The commercial unit has distillate productivity of about 2.76 L/d under cumulative solar radiation intensity of 24.37 MJ/m 2 d and it increased up to 6.03 L/d with the addition of black dye and thermocol insulation. Yearly average distillate production rate, thermal efficiency, and exergy efficiency of the improved version is about 4.36 L/d, 53.62%, and 6.89%, respectively. The greenhouse payback time of the commercial unit and insulated commercial unit with black dye is about 2.39 and 1.81 Years, respectively. Global warming potential, acidification potential and photochemical oxidant formation potential of the commercial unit decreased from 0.27 to 0.12 kg of carbon di-oxide eq/L of distillate, 2.40 to 1.05 g of sulphur di-oxide eq/L of distillate and 0.73 to 0.32 g of ethylene eq/L of distillate, respectively with the incorporation of low-cost improvement techniques. The sustainability index of the improved version is around 5.94% higher than the sustainability index of the commercial unit. The distillate production cost of improved version (1.32 INR/L) is closer to reverse osmosis (RO) water supplied to Indian houses (1.00 INR/L). The incorporation of low-cost improved techniques to the commercial unit makes it an attractive option for sustainable potable water production. However, proper marketing and awareness strategies must be adopted by stakeholders to make this improved version acceptable among the public. Highlights: Potable water productivity of commercial solar stills is low. Insulating basin to enhance productivity increases environmental impacts. Sustainability of improved version of improved unit is about 1.08 Global warming potential, acidification potential and human toxicity potential is about 0.21 kg of CO2 eq/L of distillate, 1.82 g of SO2 eq/L of distillate and 2.15 g of DCB eq/L of distillate. Distillate production cost ranges between 1.32 and 2.15 INR/L.